Using Individualized Photobooks to Enhance 3- and 4-Year-Old Children’s Science Identity Through a Science Outreach Program - Howitt, Christine; Rennie, Léonie J. (Frontiers in Education, 2021)
This paper describes how individualised photobooks were used to support 3- and 4-year old children in demonstrating their science learning and developing their science identity through participation in a science outreach program. Photographic images stimulate children’s visual thinking and allow them to provide explanations of complex concepts using their language, thus supporting children at their level of understanding. Twenty child/parent dyads were video-recorded interacting with the exhibits during a Science Outreach program into Western Australian community playgroups. Screen shots from the video-recordings were used to develop individual photobooks for each child. One week after the program, the photobooks were used in a photo-elicitation conversation with the children (accompanied by their parents) about how the exhibits worked. Children took their photobooks home and seven weeks after the program parents were interviewed about how the photobooks were used. The photobooks were found to assist the children in demonstrating their science understandings by providing a context for conversation and allowing the children to show their competence, use multiple forms of communication (verbal, non-verbal and through parent), and participate or withdraw on their terms. At home, the photobooks were found to be a focus for the children to share their knowledge of the Outreach program with family members, give the children a voice, and provide them with time to express their understandings. Having the child as narrator of his/her story and the adult as listener empowered the child’s sense of identity. The use of individualised photobooks was found to contribute to the development of the children’s identity and increase their agency in science and enhanced the parents’ perceptions of their children as young scientists.